The Effect of Tablets Effervescent Cocoa Pod Husk Extract (Theobroma Cacao L.) as a Denture Cleanser Against the Growth of Candida Albicans on Thermoplastic Nylon Plate - Ramadhanti , Arum; Achmad Gunadi; Dewi Kristiana; Afif Surya Adena (International Journal of Medical Science and Clinical Research Studies, 2025)
Denture stomatitis is a common oral health problem in denture users. It can occur due to fungal infections caused by C. albicans. An effervescent tablet is a chemical denture cleanser that can reduce plaque and microorganism accumulation, including C. albicans. The addition of natural ingredients such as cocoa pod husk extract, which contains chemical compounds like flavonoids, saponins, and tannins, has shown antifungal activity against microorganisms such as C. albicans. This research aims to determine the effect of cocoa pod husk (Theobroma cacao L.) effervescent tablets in inhibiting the growth of C. albicans after a 15-minute soaking period. The treatment groups were effervescent tablets containing cocoa pod husk extract at concentrations of 20% and 25%, polident and aquadest. The samples were thermoplastic nylon discs with a diameter of 10 mm and a thickness of 2 mm. The discs were immersed in the treatment solutions for 15 minutes and vibrated for 30 seconds using vortex, spreading 0,1ml Saboraud Dextrose Broth (SDB) on Saboraud Dextrose Agar (SDA) and incubated for 48 hours at 37°C. The number of C. albicans colonies grown on the SDA medium was counted using a colony counter. The results showed that the cocoa pod husk effervescent tablets with 25% concentration were more effective than the 20% concentration, with average colony counts of 231.8 and 372.6, respectively. The highest average C. albicans colony count was observed in the negative control group (694.8), while the lowest was in the positive control group (0). Based on the results effervescent tablets containing cocoa pod husk extract as a denture cleanser are effective in inhibiting the growth of C. albicans.